O-001 DWI-FLAIR mismatch does not predict time of stroke onset in DEFUSE 3 patients. (4th August 2020) - Slawski, D; Heit, J; Marks, M; Lemmens, R; Jakubowski, L; Mlynash, M; Lansberg, M; Albers, G
Abstract : Introduction: Acute stroke patients with unclear time of symptom onset have traditionally been ineligible for treatment with IV tissue plasminogen activator (tPA) based on a strict time window of treatment within 4.5 hours of symptom onset. Recently, the use of DWI-FLAIR mismatch to identify patients within the 4.5 hour time window has been suggested to broaden eligibility for tPA. Patients who are DWI positive and FLAIR negative qualify for treatment, while those who are both DWI and FLAIR positive are ineligible. In this study, we examined the MRI-selected patients in DEFUSE 3 and applied the rules for DWI-FLAIR mismatch ratings. DEFUSE 3 patients were all selected based on the presence of a PWI/DWI mismatch. We hypothesized that 1) inter-rater agreement is suboptimal for the detection of DWI-FLAIR mismatch; 2) the percentage of DWI-FLAIR mismatch patients is similar between known and unknown onset groups, and 3) intervention with mechanical thrombectomy (MT) yields favorable outcomes irrespective of DWI-FLAIR mismatch. Methods: This study examines the 30 patients from the DEFUSE 3 trial who were selected by PWI/DWI mismatch on MRI, rather than CT perfusion. Patients were either known to be >6 hours from symptom onset, had unknown time of symptom onset, or awoke with symptoms. Imaging was reviewed by two neuroradiologists and one vascular neurologist. Images were adjudicated in regard to whether a DWI-FLAIR mismatch was present, blinded to all other clinical and imaging data. The percentage of reader agreement was assessed. The primary endpoint was functional independence (0–2) on the 3-month modified Rankin scale. Results: 30 patients were evaluated. Of these, 3 were excluded due to poor image quality. All patients (27/27) were found to have DWI positive lesions with 100% agreement. All three readers agreed on FLAIR positivity in 9/27 patients (33% agreement). By consensus read, 15/27 patients were considered FLAIR positive (no DWI-FLAIR mismatch). Overall calculated inter-rater agreement was 72% for the detection DWI-FLAIR mismatch. In the unknown onset group, 8/14 (57%) had no DWI-FLAIR mismatch by consensus read. In the known onset group, 7/13 (54%) had no DWI-FLAIR mismatch. There were 7 patients with no DWI-FLAIR mismatch who underwent MT; 57% achieved functional independence, which compares favorably with the overall study rate of 45% in the MT group. In contrast, patients with no DWI-FLAIR mismatch who did not receive MT had a favorable outcome rate of 12.5% (1/8). Conclusions: In this study, the inter-rater agreement for detection of FLAIR-DWI mismatch among skilled readers was suboptimal. The rate of DWI-FLAIR mismatch did not differ in the known >6 hrs vs unknown onset patients. Nearly half of the patients in the known >6 hrs group did not have DWI-FLAIR mismatch, suggesting that FLAIR positivity is not a sensitive marker for being >6 hours from onset in patients with PWI/DWI mismatch. The absence of a DWI-FLAIR mismatch does not preclude a favorable DWI/PWI mismatch or favorable outcomes following late-window MT. Disclosures: D. Slawski: None. J. Heit: None. M. Marks: None. R. Lemmens: None. L. Jakubowski: None. M. Mlynash: None. M. Lansberg: None. G. Albers: None.